Moral judgement and aggressiveness in children and adolescents with intellectual disability. Issue 2 (30th May 2019) - Oubrahim, Leïla; Combalbert, Nicolas; Salvano-Pardieu, Véronique
Abstract : Purpose: The purpose of this paper is to investigate the prevalence of aggressive behaviour among children and adolescents with intellectual disability (ID) and to demonstrate a possible link with moral judgement. Design/methodology/approach: This study was carried out using two scales on a sample of 60 young people with ID in specialized schools. The first scale was "Behavior Problems Inventory-Short Form" (Rojahn et al., 2012) used to assess the frequency of aggressive behaviour and the second involved several scenarios about social situations of aggressiveness to assess moral judgement. Findings: The main findings indicate that children and adolescents with ID gave more importance to the factor "consequences" than to that of "intent". Moreover, there was a link between moral judgement and aggressive behaviour. Indeed, aggressive people found it harder to take into account the other's point of view. Regarding moral judgement, they gave greater importance to the "consequences" factor than non-aggressive people. Originality/value: The study aimed to establish, for the first time, a link between aggressiveness and moral judgement (blame) in ID (Anderson, 1996 ). This study clearly provides useful information regarding public health for patients, professionals and families. The authors were able to measure a similar frequency of aggressive behaviour in both children and adolescents with ID. The authors also highlighted a link between these aggressive behaviours and moral judgement. This knowledge should enhance understanding of manifestations of aggressiveness in this population, and improve diagnostic assessment. It should also help define appropriate directions for educational interventions to prevent the onset of aggressive behaviour or delinquency.